2007
DOI: 10.1002/nau.20518
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the data from free flow and intubated flow in women with urinary incontinence. What do they mean?

Abstract: Significant differences were found between the data from a FF and an IF in women with urinary incontinence. These findings bring to the fore the impact of the transurethral catheter and underline the necessity to obtain at least one FF and one IF during a urodynamic session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Finally, 2 recent studies on this subject confirmed these previous findings. 17,18 On the contrary, Lose and colleagues reported no difference between the Q max of 60 symptomatic women when two 5 Fr catheter were used simultaneously. 19 However, voided volume was significantly higher during the PFS than during the NIFFS.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, 2 recent studies on this subject confirmed these previous findings. 17,18 On the contrary, Lose and colleagues reported no difference between the Q max of 60 symptomatic women when two 5 Fr catheter were used simultaneously. 19 However, voided volume was significantly higher during the PFS than during the NIFFS.…”
Section: Discussionmentioning
confidence: 98%
“…Some results have been obtained: (1) correlation of the VBN parameter pucp (prostatic urethral counter-pressure) with the Abrams-Griffiths number, obstructive coefficient (OCO) and urethral resistance factor (URA) [2]; (2) creation of the VBN parameter k for detrusor contractility with both a modified projected isometric value (PIP) and the Watt factor [2]; (3) definition of an index of voiding dysfunction (D) for patients with BPE [7]; (4) demonstration of the effect of a urethral catheter on voiding [8]; (5) assessment of an alpha-blocker treatment for BPE and of surgery for incontinence with suburethral tapes [9].…”
Section: Initial Vbn Modelmentioning
confidence: 99%
“…Direct interpretation is relatively limited using this formula compared with 89% interpretability for the Liverpool nomograms (15-600 mL). Valentini et al [5] recently noted that free (nonintubated) urofl owmetry studies should be used to interpret urofl ow and PVR parameters, as intubation urofl owmetry (pressure catheter in situ) is associated with a greater level of abnormality of both parameters.…”
Section: Defi Ning Abnormal Voiding Function In Womenmentioning
confidence: 99%